Reconstruction of Corporate Governance Legal System with Governance, Risk Management, and Compliance (GRC) Approach - Rebecca Pariela, Eunike Petra; Suparno, Suparno (Pelopor Publikasi Akademika, 2024)
This research aims to evaluate and propose a reconstruction of the corporate governance legal system in Indonesia using the Governance, Risk Management, and Compliance (GRC) approach to enhance governance quality and sustainability. The study identifies existing legal gaps and challenges that hinder effective GRC integration, including regulatory ambiguities, lack of stakeholder understanding, and weak enforcement mechanisms. The research adopts a normative legal method, combining legislative and analytical approaches to evaluate laws such as the Limited Liability Company Law (UU PT) and Financial Services Authority (OJK) regulations. Findings reveal that current regulations focus primarily on compliance without adequately integrating risk management and governance aspects, leading to suboptimal corporate performance. The study proposes regulatory reforms, including the introduction of specific GRC guidelines, and strategies for increasing stakeholder awareness through training and public campaigns. These measures are expected to strengthen corporate governance, enhance accountability, and foster sustainable economic growth by aligning governance practices with global standards. The research concludes that a comprehensive GRC framework is crucial for addressing legal gaps, ensuring transparency, and building resilience in Indonesia’s corporate sector.